RELATIONSHIP BETWEEN MANGOSTEEN LEAF NITROGEN CONTENTS AND LEAF SPAD VALUES - Eko Setiawan (Universitas Trunojoyo Madura, 2014)
We investigated nitrogen contents on mangosteen leaf and related on leaf SPAD value. The experiment was conducted using mangosteen trees grown in commercial orchard in Bogor, Indonesia during May to October 2010. Mangosteen trees of 3 different ages, young (20-year-old), middle-aged (35-year-old), and old (50-year-old) trees, each of five trees, were selected for study, and the canopy of each tree was divided into 9 sectors based on height (bottom, middle, top) and width (inner, center, outer). SPAD values had a negative correlation with leaf N content in all ages and could be explained by regressionl equations N level (% DW) = -0.0099 × SPAD + 2.2366; R² = 0.91; N level (% DW) = -0.0177 × SPAD + 2.8001; R² = 0.67; and N level (% DW) = -0.0187 × SPAD + 2.7785; R² = 0.45 in young, middle-aged and old trees, respectively. It is suggested that the SPAD value determined by a portable chlorophyll meter can be used to obtain a quick estimation of mangosteen leaf N status. Keywords: age, fruiting position, Garcinia mangostana L., nitrogen, SPAD